Polymorphisms of glutathione-S-transferase M1, T1, P1 and the risk of prostate cancer: a case-control study - Račay Peter; Hatok Jozef; Matáková Tatiana; Dobrota Dušan; Waczulíková Iveta; Sivoňová Monika; Kliment Ján (Journal of Experimental & Clinical Cancer Research, 2009)
Abstract Background It has been suggested that polymorphisms in glutathione-S-transferases (GST) could predispose to prostate cancer through a heritable deficiency in detoxification pathways for environmental carcinogens. Yet, studies linking GST polymorphism and prostate cancer have so far failed to unambiguously establish this relation in patients. A retrospective study on healthy, unrelated subjects was conducted in order to estimate the population GST genotype frequencies in the Slovak population of men and compare our results with already published data (GSEC project-Genetic Susceptibility to Environmental Carcinogens). A further aim of the study was to evaluate polymorphisms in GST also in patients with prostate cancer in order to compare the evaluated proportions with those found in the control subjects. Methods We determined the GST genotypes in 228 healthy, unrelated subjects who attended regular prostate cancer screening between May 2005 and June 2007 and in 129 histologically verified prostate cancer patients. Analysis for the GST gene polymorphisms was performed by PCR and PCR-RFLP. Results We found that the GST frequencies are not significantly different from those estimated in a European multicentre study or from the results published by another group in Slovakia. Our results suggest that Val/Val genotype of GSTP1 gene could modulate the risk of prostate cancer, even if this association did not reach statistical significance. We did not observe significantly different crude rates of the GSTM1 and GSTT1 null genotypes in the men diagnosed with prostate cancer and those in the control group. Conclusion Understanding the contribution of GST gene polymorphisms and their interactions with other relevant factors may improve screening diagnostic assays for prostate cancer. We therefore discuss issues of study feasibility, study design, and statistical power, which should be taken into account in planning further trials.